2018
DOI: 10.1111/pce.13128
|View full text |Cite
|
Sign up to set email alerts
|

Glandular trichomes as a barrier against atmospheric oxidative stress: Relationships with ozone uptake, leaf damage, and emission of LOX products across a diverse set of species

Abstract: There is a spectacular variability in trichome types and densities and trichome metabolites across species, but the functional implications of this variability in protecting from atmospheric oxidative stresses remain poorly understood. The aim of this study was to evaluate the possible protective role of glandular and non-glandular trichomes against ozone stress. We investigated the interspecific variation in types and density of trichomes and how these traits were associated with elevated ozone impacts on vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 87 publications
(188 reference statements)
3
84
0
Order By: Relevance
“…Detailed chemical analyses showed that the contents of the major triterpenoid and flavonoid aglycones correlated positively with glandular trichome density, indicating that glandular trichomes strongly affect leaf surface chemistry, and thus, hydrophobic properties and resistance traits to herbivores and pathogens. In this issue, Li et al () have examined the protective role of glandular and nonglandular trichomes against ozone stress covering a diverse set of plant species with different trichome types. Responsiveness of glandular trichomes to ozone has been previously reported, for example, by Pääkkönen, Günthardt‐Goerg, and Holopainen () and Prozherina et al () in silver birch leaves.…”
Section: Trichomes Are Responsive To Many Environmental Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Detailed chemical analyses showed that the contents of the major triterpenoid and flavonoid aglycones correlated positively with glandular trichome density, indicating that glandular trichomes strongly affect leaf surface chemistry, and thus, hydrophobic properties and resistance traits to herbivores and pathogens. In this issue, Li et al () have examined the protective role of glandular and nonglandular trichomes against ozone stress covering a diverse set of plant species with different trichome types. Responsiveness of glandular trichomes to ozone has been previously reported, for example, by Pääkkönen, Günthardt‐Goerg, and Holopainen () and Prozherina et al () in silver birch leaves.…”
Section: Trichomes Are Responsive To Many Environmental Factorsmentioning
confidence: 99%
“…Li et al () used a step‐wise increase in ozone exposure to cause an acute oxidative stress treatment. Ozone fumigation is technically easy to manipulate within leaf chamber systems, allowing strict control of the experimental procedures.…”
Section: Connecting Trichomes To Plant Function and Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations